Association Between Gestational Weight Gain and Autism Spectrum Disorder in Offspring: A Meta‐Analysis. Issue 11 (1st October 2020) - Su, Le; Chen, Cheng; Lu, Liping; Xiang, Anny H.; Dodds, Linda; He, Ka
Abstract : Objective: This study aimed to quantitatively examine the association between gestational weight gain (GWG) and risk of autism spectrum disorder (ASD) in offspring. Methods: Electronic databases were searched for studies of excessive or inadequate GWG, as compared with recommended GWG, in relation to the risk of ASD in offspring. Measures of the association from primary studies were pooled using a meta‐analytic approach and expressed as weighted odds ratios (ORs) with 95% CIs. Results: Nine studies were identified, including 323, 253 participants with 4, 135 cases of ASD from five cohort studies and 1, 462 cases and 3, 265 controls from four case‐control studies. Evidence from cohort studies indicates that both excessive and inadequate GWG was significantly associated with a higher risk for ASD in offspring. The pooled OR of ASD was 1.10 (95% CI: 1.02‐1.18) for excessive GWG and 1.13 (95% CI: 1.04‐1.24) for inadequate GWG using recommended GWG as the reference. Evidence from case‐control studies suggests that excessive GWG (1.38 [95% CI: 1.19‐1.62]) but not inadequate GWG (0.87 [95% CI: 0.72‐1.04]) was significantly associated with a higher risk for ASD. Conclusions: The accumulated evidence has supported that gaining weight outside the recommended GWG is associated with a higher risk for ASD in offspring.